2015
DOI: 10.1785/0120140149
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Coda‐Wave Attenuation in the Central and Eastern Alborz, Iran

Abstract: The quality factor of coda (Q c ) waves has been estimated by using single backscattering and single isotropic scattering models. The earthquakes used were recorded by three permanent and one temporary network located in the central and eastern Alborz, Iran. The database was composed of 746 local earthquakes with local magnitude from 1.1 to 5.7. The estimated Q c has been found to be similar for lapse times greater than twice the S-wave travel time (2t S ) for both methods.The estimated Q c for central frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…This value is normally never changed. Other studies use a fixed rms window (e.g., Farrokhi et al, 2015) of 2-5 s. It should be long enough to smooth out the envelope but not so long as to completely ruin the shape of the envelope. Tests were made with three and seven cycles as well as fixed lengths (Table 6) and it can be observed that the length of the rms window affects Q 0 but less so Q 10 .…”
Section: The Length Of the Rms Windowmentioning
confidence: 99%
See 3 more Smart Citations
“…This value is normally never changed. Other studies use a fixed rms window (e.g., Farrokhi et al, 2015) of 2-5 s. It should be long enough to smooth out the envelope but not so long as to completely ruin the shape of the envelope. Tests were made with three and seven cycles as well as fixed lengths (Table 6) and it can be observed that the length of the rms window affects Q 0 but less so Q 10 .…”
Section: The Length Of the Rms Windowmentioning
confidence: 99%
“…This coda Q method can give quite different results depending on the processing parameters used. Many papers have been published that claim a close relationship between tectonics and coda Q by comparing results from different regions in which Q has been studied by different authors using different or unknown parameters, for example, Woodgold (1994), Bianco et al (1999), Zelt et al (1999), Yun et al (2007), Dobrynina (2011), andFarrokhi et al (2015). However, because all the processing parameters are rarely, if ever, given, and different parameters can lead to different results, there might not be much substance to those claims.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Motaghi and Ghods (2012) studied the attenuation of ground-motion spectral amplitudes and its variations across the central Alborz Mountains. Rahimi et al (2010) and Farrokhi et al (2015) estimated coda-wave attenuation in the central and eastern Alborz. Farrokhi and Hamzehloo (2016) investigated body wave attenuation…”
Section: Introductionmentioning
confidence: 99%